AMPK‐regulated miRNA‐210‐3p is activated during ischaemic neuronal injury and modulates PI3K‐p70S6K signalling. Issue 4 (18th March 2021) - Pfeiffer, Shona; Tomašcová, Anna; Mamrak, Uta; Haunsberger, Stefan J.; Connolly, Niamh M. C.; Resler, Alexa; Düssmann, Heiko; Weisová, Petronela; Jirström, Elisabeth; D'Orsi, Beatrice; Chen, Gang; Cremona, Mattia; et al.
Abstract: Progressive neuronal injury following ischaemic stroke is associated with glutamate‐induced depolarization, energetic stress and activation of AMP‐activated protein kinase (AMPK). We here identify a molecular signature associated with neuronal AMPK activation, as a critical regulator of cellular response to energetic stress following ischaemia. We report a robust induction of microRNA miR‐210‐3p both in vitro in primary cortical neurons in response to acute AMPK activation and following ischaemic stroke in vivo . Bioinformatics and reverse phase protein array analysis of neuronal protein expression changes in vivo following administration of a miR‐210‐3p mimic revealed altered expression of phosphatase and tensin homolog (PTEN), 3‐phosphoinositide‐dependent protein kinase 1 (PDK1), ribosomal protein S6 kinase (p70S6K) and ribosomal protein S6 (RPS6) signalling in response to increasing miR‐210‐3p. In vivo, we observed a corresponding reduction in p70S6K activity following ischaemic stroke. Utilizing models of glutamate receptor over‐activation in primary neurons, we demonstrated that induction of miR‐210‐3p was accompanied by sustained suppression of p70S6K activity and that this effect was reversed by miR‐210‐3p inhibition. Collectively, these results provide new molecular insight into the regulation of cell signalling during ischaemic injury, and suggest a novel mechanism whereby AMPK regulates miR‐210‐3p to control p70S6K activity in ischaemic stroke and excitotoxic injury. Abstract : Progressive neuronal injury following ischaemic stroke is associated with energetic stress and AMP‐activated protein kinase (AMPK) activation. We aimed to explore AMPK‐regulated microRNAs as modulators of key downstream pathways in the regulation of neuronal fate. We identified microRNA‐210 as significantly up‐regulated in response to AMPK‐activation in primary neurons in vitro and following ischaemic stroke in vivo . We report multi‐targeting regulation of PI3K‐p70S6K signalling by miR‐210 and confirm decreased p70S6K in response to increased miR‐210 in vivo . We suggest a novel mechanism whereby AMPK regulates miR‐210 to control p70S6K activity in response to excitotoxic neuronal injury, allowing for restoration of energy homeostasis.